Times, institutions, subjects change: reflections on the significance of learning experiences in Buenos Aires secondary schools (Praxis Educativa, 2022)
The purpose of this article is to reflect on the significance of school learning experiences from the perspective of a group of young secondary school students from a town in the province of Buenos Aires. The reflection and analysis is part of the research results obtained from inquiries carried out before and during the Covid-19 pandemic. They seek to address the production conditions of school learning that are identified by the student population as promoters of significance. Their voices become relevant data to problematize the pedagogical encounter in contemporary times, emphasizing the intersubjective and cultural dimension that give meaning to the school experience
Keywords: secondary school; changes; youths; experiences; significance